CARBON EMISSION DISCLOSURE: DITINJAU DARI MEDIA EXPOSURE, KINERJA LINGKUNGAN DAN KARAKTERISTIK PERUSAHAAN GO PUBLIC BERBASIS SYARIAH DI INDONESIA - Bayu Tri Cahya (Nizham Jurnal Studi Keislaman, 2016)
Carbon emission disclosure is a disclosure to assess an organisation's carbon emissions and set targets for reduction of the carbon emission. This study is aimed to obtain empirical evidence about the influence of environmental performance, media exposure, type of industry, size of company, and profitability to the extent of carbon emission disclosure in Indonesian shariah companies. To measure the extent of carbon emission disclosure, it is used checklist that has been developed based on the information inquiry forms provided by the Carbon Disclosure Project (CDP). This study employed purposive sampling method from companies listed in Jakarta Islamic Index (JII) in 2012-2014. There were 35 companies which fulfilled criterion as the research samples. The results of this study showed that type of industry has negative significance and profitability has positive significance to influence the extent of carbon emission disclosure. Whilst, environmental performance, media exposure and the size of company has no significant influence to the extent of carbon emission disclosure.